Basophil Activation-Dependent Autoantibody and Interleukin-17 Production Exacerbate Systemic Lupus Erythematosus - Pan, Qingjun; Gong, Li; Xiao, Haiyan; Feng, Yongmin; Li, Lu; Deng, Zhenzhen; Ye, Ling; Zheng, Jian; Dickerson, Carol A.; Ye, Lin; An, Ning; Yang, Chen; et al. (Frontiers in Immunology, 2017)
Objective Autoantibody and inflammatory cytokines play crucial roles in the development of systemic lupus erythematosus (SLE); however, the regulation of their production warrants further investigation. This study aimed to investigate the role of basophil activation in the development of SLE based on studies in patients with SLE and spontaneous lupus-prone MRL-lpr/lpr mice. Methods The phenotypes of peripheral basophils and the production of autoantibody and interleukin (IL)-17 in patients with SLE were determined by flow cytometry and enzyme-linked immunosorbent assay, and also their correlations were investigated by statistical analysis. Thereafter, the effect of basophils on autoantibody production by B cells and Th17 differentiation in SLE were evaluated in vitro. Finally, the effect of basophil depletion on the development of autoimmune disorders in spontaneous lupus-prone MRL-lpr/lpr mice was examined. Results The decreased numbers and an increased activation of peripheral basophils were found to be correlated with increased autoantibody production and disease activity in patients with SLE. Correspondingly, in vitro coculture studies showed that basophils obtained from patients with SLE promoted autoantibody production by SLE B cells and promoted Th17 differentiation from SLE naïve CD4+ T cells. The decrease of peripheral basophils in patients with SLE might be due to their migration to lymph nodes post their activation mediated by (autoreactive) IgE as supported by their increased CD62L and CCR7 expressions and accumulation in the lymph nodes of MRL-lpr/lpr mice. Furthermore, an increased activation of peripheral basophils was identified in MRL-lpr/lpr mice. Importantly, basophil-depleted MRL-lpr/lpr mice exhibited an extended life span, improved renal function, and lower serum levels of autoantibodies and IL-17, while basophil-adoptive-transferred mice exhibited the opposite results. Conclusion These finding suggest that basophil activation-dependent autoantibody and IL-17 production may constitute a critical pathogenic mechanism in SLE.